Warren, Phil. Phil's sculpture of a goat and horncat done by Esau George. - Barrett, Terra (2017)
Photo part of The Goats of New Perlican Project. A partnership between the Heritage Foundation of Newfoundland and Labrador and Heritage New Perlican.